2009
DOI: 10.1111/j.1751-2980.2008.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood concentration of pantoprazole sodium is significantly high in hepatogenic peptic ulcer patients, especially those with a poor CYP2C19 metabolism

Abstract: OBJECTIVE:  To determine the plasma concentration of pantoprazole sodium by high performance liquid chromatography and its distribution in patients with different CYP2C19 genotypes in an attempt to provide experimental data for the clinical dosage adjustment of the drug. METHODS:  Patients with liver disease and associated peptic ulcer were genotyped according to their CYP2C19 wild‐type sequences and mutations in CYP2C19m1 and CYP2C19m2 by the principles of the American Surgical Association using polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…This finding is in line with data reported by Sim et al [12], who estimated that CYP2C19*17 homozygotes would attain up to 40% lower omeprazole AUC values than subjects homozygous for the CYP2C19*1 allele after a single dose of the drug. Similar to our observations, higher pantoprazole concentrations in poor CYP2C19 metabolizers have been reported by others [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in line with data reported by Sim et al [12], who estimated that CYP2C19*17 homozygotes would attain up to 40% lower omeprazole AUC values than subjects homozygous for the CYP2C19*1 allele after a single dose of the drug. Similar to our observations, higher pantoprazole concentrations in poor CYP2C19 metabolizers have been reported by others [11].…”
Section: Discussionsupporting
confidence: 93%
“…It was demonstrated that PPI-based eradication therapy is more effective, not only in PMs, but also in intermediate metabolizers (IM), heterozygotes with one wild-type and one defective CYP2C19 allele, compared with wild-type homozygotes (rapid extensive metabolizers) [8][9][10]. In PMs and IMs mean plasma levels of PPIs are higher, what makes therapy with standard drugs' doses more effective compared with wild-type homozygotes [11]. Recently, a novel CYP2C19 gene variant (CYP2C19*17), associated with increased gene transcription, and thus faster metabolism of CYP2C19 substrates was described [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus interactions of anthocyanins and CYP2C19 are not to be expected unless hepatic function is severely compromised or enzyme functionality is otherwise impaired, e.g. by inactivating genetic variation (Shao et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It is not uncommon to construct calibration curves that cover a more than 100-fold range in order to characterize the pharmacokinetics from starting low human doses to the anticipated maximum tolerated dose (MTD) in fi rst-in-man clinical protocols and also for application in bioequivalence/pharmacokinetic studies (Vijaya Bharathi et al, 2009;Zhang and Chen, 2009;Tang et al, 2009;Zeng et al, 2009;Jiang et al, 2009;Arnold et al, 2008;Handy et al, 2008;Minkin et al, 2008;Jain et al, 2008;Xue et al, 2007;Zeng et al, 2007;Xu et al, 2007;Shen et al, 2004;Upreti et al, 2003). Additionally, the existence of a 100-fold range may be useful when dealing with NCEs that are substrates for polymorphic cytochrome P450 (CYP) isozymes wherein logorders of diff erences in the plasma concentrations of the parent and/or metabolite are expected to occur between the extensive metabolizer and poor metabolizer phenotypes (Preskorn et al, 2009;Shao et al, 2009;Davies et al, 2008;Stamer et al, 2007;Shilbayeh and Tutunji, 2006;Inomata et al, 2005).…”
Section: Introductionmentioning
confidence: 98%